Overexpression of connective tissue growth factor WISP-1 in Chinese primary rectal cancer patients - Tian, Chao (World J Gastroenterol, 2007)
AIM: To clarify the expression change of Wnt-induced secreted protein-1 (WISP-1) in human rectal cancer and to determine whether it is correlated with invasion and metastasis of human rectal cancer. METHODS: Eighty-six paired samples of rectal cancer and surgically resected distant normal rectal tissue were collected and allocated into cancer group and control group respectively. WISP-1 mRNA was detected by relative quantitative real-time RT-PCR and WISP-1 protein was examined by immunohistochemical staining. RESULTS: WISP-1 gene overexpression was found in 65% (56/86) primary rectal cancers, 2-30 times that of the level in normal matched rectal tissues (P = 0.001). The mRNA expression level was correlated with Duke’s staging, histological differentiation grade and lymph node status. The WISP-1 protein expression was in accordance with mRNA expression level. The positive degree of immunohistochemical staining in the cancer group (1.40 ± 0.35) was different from that in control group (1.04 ± 0.08, P < 0.001). Moreover, in cancer group the positive staining degree in high-level mRNA cancers (1.46 ± 0.37, n = 56) was higher than that in low-level mRNA (1.28 ± 0.28, n = 30, P = 0.018). CONCLUSION: Aberrant levels of WISP-1 expression may play a role in rectal tumorigenesis. WISP-1 may be used as a specific clinical diagnosis and prognosis marker in rectal cancer.